2007
DOI: 10.1111/j.1476-4431.2007.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between point‐of‐care glucometry, blood gas and laboratory‐based measurement of glucose in an equine neonatal intensive care unit

Abstract: Objective: To test the agreement between 3 common methods of glucose measurement in a population of critically ill foals presenting to a neonatal intensive care unit. Design: Prospective clinical study. Setting: University large animal hospital neonatal intensive care unit. Animals: Sequentially admitted critically ill neonatal foals <30 days of age. Interventions: Venous blood obtained from a jugular vein was used for determination of blood glucose concentration using point‐of‐care (POC) glucometry (GLU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…A recent study of glucometry in the critically ill equine neonate clearly demonstrated the need for thorough investigation of glucometry in veterinary patients. In that study, POC glucometry with whole blood was, on average, 20 mg/dL below the laboratory standard and 33 mg/dL below measurements with a multielectrode blood gas analyzer 8 . In addition, the 95% limits of agreement of the glucometer tested were extremely wide, 8 demonstrating that the glucometer had less than ideal agreement with the laboratory standard, and may therefore be inappropriate for use in a clinical setting.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…A recent study of glucometry in the critically ill equine neonate clearly demonstrated the need for thorough investigation of glucometry in veterinary patients. In that study, POC glucometry with whole blood was, on average, 20 mg/dL below the laboratory standard and 33 mg/dL below measurements with a multielectrode blood gas analyzer 8 . In addition, the 95% limits of agreement of the glucometer tested were extremely wide, 8 demonstrating that the glucometer had less than ideal agreement with the laboratory standard, and may therefore be inappropriate for use in a clinical setting.…”
Section: Discussionmentioning
confidence: 78%
“…Other factors that may affect accuracy include alterations of the filters used in glucometer strips to separate the red blood cells from plasma. These may be affected by the increased tendency of equine red blood cells to rouleaux formation and, in addition, microclot formation, hemolysis, or inflammatory phenomena such as high fibrinogen concentration 8,25 . Reagent test strip performance may vary by lot and individual monitors by model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presenting complaints for horses considered healthy on admission included nonseptic, noncatastrophic limb injury (11), lameness examination (8), dental examination (3), pre-operative cryptorchidectomy or ovariectomy (2), and head shaking (1). Presenting complaints for horses admitted for emergency evaluation and considered critically ill included colic (15), severe local sepsis with concurrent signs of systemic illness (3), retained placenta (2), placentitis (1), colitis (1), laminitis (1), influenza-associated acute respiratory distress syndrome (1), and acute blood loss (1). Foals had a median age of 4 days [IQR: 1-6 days].…”
Section: Resultsmentioning
confidence: 99%